Benzimidazole-BODIPY as optical and fluorometric pH sensor. (May 2016) - Li, Zhensheng; Li, Lei-Jiao; Sun, Tingting; Liu, Liming; Xie, Zhigang
Abstract: A new optical and fluorometric pH sensor has been obtained by attaching pH sensitive group benzimidazole at the 2-position of borondipyrromethene. Due to the electron-donor effect, benzimidazole group caused obvious bathochromic shift in the absorption and fluorescence spectra. Upon protonation, the solution exhibited drastic blue-shifted absorption and enhanced fluorescence, and the color changed from yellow to green simultaneously. The sensing mechanism was elucidated by quantum chemistry calculation approach. Cell experiments were carried out to verify the compound could selectively locate in the acidic lysosome. These results indicated the Benzimidazole-BODIPY could be used as an optical and "off-on" fluorescent pH indicator. Graphical abstract: Highlights: A novel optical and fluorescent pH sensor has been obtained by facile synthetic procedure. The sensing mechanisms were elucidated by density functional theory calculation. The sensor could selectively image lysosome in living cells.